Tafseer Tarbawi Al-Qur'an Surah Al-Jumu'ah Verse 2 and Its Implementation in Education - Aida, Sugesti Riza Nor; Arif, Mahmud (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2022)
The concept of educational goals in the Qur'an must be implemented. In other words, the concept of educational goals must be able to realize the educational design described in the book of the Qur'an, especially in Q.S. Al-Jumu'ah verse 2. This article discuss the Q.S. Al-Jumu'ah verse 2 and its implications for education. The approach in this study uses a qualitative approach. The type of research used in this research is library research. Data collection techniques using documentation techniques sourced from primary data and secondary data for further data analysis using descriptive analysis. The result of this research is the interpretation of Surah Al-Jumu'ah Verse 2 is by sending Allah's messenger to mankind, aiming to complete the education of science and morals as well as faith from the book. Then education, learning and skills are forms of internalization for self-potential development as part of the task of an educator. And educators must understand the concept of educational goals and have 3 teacher competencies (cognitive, affective and psychomotor). Konsep tujuan pendidikan dalam Qur’an harus diimplementasikan, dengan kata lain, konsep tujuan pendidikan harus mampu mewujudkan desain pendidikan yang dijelaskan dalam kitab Al-Qur'an, terutama dalam Q.S. Al-Jumu’ah ayat 2. Artikel ini akan membahas tentang Q.S. Al-Jumu’ah ayat 2 beserta implikasinya pada pendidikan. Pendekatan dalam penelitian ini menggunakan pendeketan kualitatif. Jenis penelitian yang digunakan penelitian ini adalah menggunakan studi pustaka (library research). Teknik pengumpulan data dengan menggunakan teknik dokumentasi yang bersumber dari data primer dan data sekunder untuk selanjutnya analisis data menggunakan analisis depskriptif. Hasil penelitian ini adalah tafsiran Surat Al-Jumu’ah Ayat 2 ini adalah dengan diutusnya utusan Allah kepada umat manusia, bertujuan untuk melengkapi pendidikan ilmu dan akhlak serta keimanan dari kitab. Kemudian Pendidikan, pembelajaran dan keterampilan adalah bentuk-bentuk internalisasi untuk pengembangan potensi diri sebagai bagian dari tugas seorang pendidik.dan pendidik harus memahami konsep tujuan Pendidikan serta memiliki 3 kompetensi guru (kognitif, afektif dan psikomotorik).